2011
DOI: 10.4330/wjc.v3.i1.1
|View full text |Cite
|
Sign up to set email alerts
|

Cardiorenal syndromes

Abstract: Cardiorenal syndromes (CRS) have been subclassified as five defined entities which represent clinical circumstances in which both the heart and the kidney are involved in a bidirectional injury and dysfunction via a final common pathway of cell-to-cell death and accelerated apoptosis mediated by oxidative stress. Types 1 and 2 involve acute and chronic cardiovascular disease (CVD) scenarios leading to acute kidney injury or accelerated chronic kidney disease. Types 2 and 3 describe acute and chronic kidney dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
31
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 49 publications
3
31
0
Order By: Relevance
“…It is also known that the presence of CKD increases severity, worsens the response to treatment, and is associated with poor cardiac and renal outcomes in cardiorenal syndrome. 4,5 The renin-angiotensin system (RAS) has a critical role in the development of cardiovascular and renal disease in a clinical setting. It has been reported that the role of RAS in congestive heart failure (CHF) and CKD is complex owing to involvement of multiple peptides and receptors.…”
mentioning
confidence: 99%
“…It is also known that the presence of CKD increases severity, worsens the response to treatment, and is associated with poor cardiac and renal outcomes in cardiorenal syndrome. 4,5 The renin-angiotensin system (RAS) has a critical role in the development of cardiovascular and renal disease in a clinical setting. It has been reported that the role of RAS in congestive heart failure (CHF) and CKD is complex owing to involvement of multiple peptides and receptors.…”
mentioning
confidence: 99%
“…Decreased cardiac output also activates the renin-angiotensin-aldosterone system and the sympathetic nervous system, which in turn causes congestion and constriction in afferent arterioles. These results in further decreases in renal perfusion pressure (34). Theoretically, the above-mentioned pathophysiological mechanism is valid; however, recent studies suggest different mechanisms.…”
Section: Discussionmentioning
confidence: 93%
“…Deterioration of this close interrelation between these two organ systems is known as "cardio-renal syndrome," and studies in HF have clarified the pathophysiological mechanisms behind this syndrome. It has been thought that renal dysfunction in HF is attributable to low cardiac output, which consequently causes reduction in blood flow and renal perfusion pressure (9,34). Decreased cardiac output also activates the renin-angiotensin-aldosterone system and the sympathetic nervous system, which in turn causes congestion and constriction in afferent arterioles.…”
Section: Discussionmentioning
confidence: 99%
“…Siderocalin has been shown to be elevated in patients with ADHF predicting the need for renal replacement therapies and or death [72]. It is unknown at present whether or not NGAL could serve as a therapeutic target either via infusion of recombinant protein or molecular mimicry with the intent of reducing oxidative stress results in cell dysfunction, accelerated apoptosis, and cell death, and fibrosis [73]. One such molecular approach, using an NGAL-like agent to bind available tissue catalytic iron is with the mild iron chelator oral deferiprone, is an attractive therapeutic target from a conceptual standpoint.…”
Section: Non-hemodynamic Factorsmentioning
confidence: 99%